Responsibilities of Notaries in Making Deeds Affecting Bad Credit at Bank Rakyat Indonesia - Ady, Sigit Priambodo; Bawono, Bambang Tri (TABELLIUS: Journal of Law, 2023)
This study aims to analyze: 1) Implementation of the making of the credit agreement deed at Bank Rakyat Indonesia. 2) The responsibility of a notary in making a deed that has an impact on bad credit at Bank Rakyat Indonesia. The approach method in this research is a sociological juridical approach. The specification of the research used is descriptive analytical research. Types of data using primary and secondary data. Data collection by interview method and literature study. The data analysis method used is qualitative analysis. The results of the study concluded: 1) The implementation of making a credit agreement deed at Bank Rakyat Indonesia is carried out based on an agreement between the debtor and the creditor. After the credit agreement is signed by the debtor and the party representing BRI, then waarmerking will be carried out by a Notary appointed by PT. Bank Rakyat Indonesia (Persero) Tbk. The credit agreement deed is notarized, the binding is carried out simultaneously with the binding of collateral / Mortgage. In granting the Mortgage before the PPAT, it must be attended by the Mortgage Giver and the Mortgage recipient and witnessed by 2 (two) witnesses. 2) The responsibility of a notary in making a deed that has an impact on bad credit at Bank Rakyat Indonesia Decision Number 52/Pdt.G/2020/PN Cjr Notary cannot be directly held accountable individually, collectively, based on errors or absolute liability. This is because the notary only mewaarmeking credit agreement deed that has been agreed upon by the debtor and the party representing BRI, namely the head of the PT branch. Bank Rakyat Indonesia (Persero). Regarding collateral/guarantee, before the binding of the notary has also checked in advance regarding the correctness, so that if bad credit occurs until the auction of collateral/guarantee, it is absolutely the responsibility of the parties themselves.Keywords: Bank; Credit; Responsibility.